2020
DOI: 10.3390/app10072292
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Investigation of Gear Body-Induced Tooth Deflections and Development of an Improved Analytical Solution

Abstract: Many researchers have developed analytical methods to evaluate gear meshing stiffness. Some of these methods ignored the effect of the gear body while others used a simplified model to consider its effect. Until now, a detailed investigation of gear body-induced tooth deflections has been rare, especially for the double-tooth-pair meshing period. In this study, we present a detailed investigation of gear body-induced tooth deflections. To be specific, we will discuss how to accurately evaluate gear body-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Unfortunately, both of them ignored an important parameter-the gear's friction in their literatures. Furthermore, Zhang H [13] and Prabhu Sekar R [14] conducted a detailed investigation of gear body-induced tooth deflections which included the gear's fillet-foundation deformation through the finite element analysis and the results showed good agreement with experimental data. The lubrication conditions were emphatically considered in gear wear characteristics research [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Unfortunately, both of them ignored an important parameter-the gear's friction in their literatures. Furthermore, Zhang H [13] and Prabhu Sekar R [14] conducted a detailed investigation of gear body-induced tooth deflections which included the gear's fillet-foundation deformation through the finite element analysis and the results showed good agreement with experimental data. The lubrication conditions were emphatically considered in gear wear characteristics research [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 98%
“…Fig 13. Torsional Vibration Analysis in Time/Frequency-domain under 40% Rated Torque…”
mentioning
confidence: 99%
“…Sainsot et al 21 presented an improved formula by using Muskhelishvili theory in the formula for gear foundation stiffness suggested by Weber 13 and Cornell. 14 Zhang et al 22 showed more improved results by modifying the coefficients suggested by Sainsot et al 21 through a detailed FEM.…”
Section: Introductionmentioning
confidence: 99%